EXCHANGE RATE TARGET ZONES: A SURVEY OF THE LITERATURE. (19th August 2011) - Portugal Duarte, António; Sousa Andrade, João; Duarte, Adelaide
Abstract This work selectively reviews the literature on exchange rate target zones and their theoretical and empirical methodologies and examines whether they can be used to clarify to what extent this type of exchange rate regime could contribute to greater exchange rate stability. We discuss the main contributions of the first and second generations of exchange rate target zone models. In an attempt to reconcile the poor empirical performance of the Krugman model with the reality of exchange rate target zone regimes, this line of research integrates target zones with alternative underlying economic models, such as imperfect credibility, intra‐marginal interventions and sticky price models. It was thus possible to understand the correlations observed between the exchange rate, its fundamentals determinants and the interest rate differential, and to explain the fact that the statistical distribution of the exchange rate is hump shaped rather than U shaped. This implies that the initial emphasis of target zone models on nonlinearities, 'honeymoon effect', 'smooth pasting' and marginal interventions has vanished. Exchange rate target zones are better described as similar to managed floating regimes with intra‐marginal interventions, with some marginal interventions when the exchange rate reaches the edges of the floating band.